2003
DOI: 10.1037/1040-3590.15.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Unipolar Depression as a Chaotic Process.

Abstract: This study inspected the deterministic structure of unipolar depression. Two women self-monitored sadness hourly 10 times a day for 6 months. One woman had a recurrent history of unipolar depression, and the other did not. Data were analyzed by visual inspection, examination of the Fourier transforms of the time plots, and the correlation dimension. Results suggested that in addition to a strong periodic component that existed only within the depressed subject's mood time series, a low-dimensional chaotic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…One research group [27] studied mood ratings in depression and found a possible underlying chaotic process. A different group [28] studied mood ratings in affective instability and found that the patients showed more variability than controls on the Mean Squared Successive Difference, while the value of the Fractal Dimension was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…One research group [27] studied mood ratings in depression and found a possible underlying chaotic process. A different group [28] studied mood ratings in affective instability and found that the patients showed more variability than controls on the Mean Squared Successive Difference, while the value of the Fractal Dimension was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a tendency over the past decade to interpret individual self-recorded mood sequences in terms of chaos theory, which would suggest that the time development of mood might be deterministic (Gottschalk et al 1995(Gottschalk et al , 1998Heiby et al 2003). The random-mood model takes an opposite point of view and has been shown to be capable of reproducing the same mood-sequence characteristics (van der Werf et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, this common-cause view has been challenged (7-9). The alternative view is that the correlated symptoms should be regarded as the result of interactions of components of a complex dynamical system (7,(10)(11)(12). Consequently, new models of the etiology of depression involve a network of interactions between components, such as emotions, cognitions, and behaviors (8,9).…”
mentioning
confidence: 99%